2009
DOI: 10.1007/s12273-009-9123-2
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation by the FVM of coupled heat transfers by conduction, natural convection and radiation in honeycomb’s hollow bricks

Abstract: This paper presents a detailed numerical study, in steady state regime, of the interaction between two dimensional heat transfers by conduction, natural convection and radiation in double hollow bricks formed by two honeycomb walls separated by an air layer. The air motion in all cavities of the system is laminar. The left and right vertical sides of the hollow bricks are considered isothermal and maintained at different constant temperatures. The top and bottom horizontal sides are assumed to be adiabatic. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The overall heat transfer through the cavity can be easily calculated from N u t , which is the sum of the Nusselt numbers given by the empirical relationships (22) and (25).…”
Section: Development Of Correlations For Heat Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…The overall heat transfer through the cavity can be easily calculated from N u t , which is the sum of the Nusselt numbers given by the empirical relationships (22) and (25).…”
Section: Development Of Correlations For Heat Transfermentioning
confidence: 99%
“…For cavities of low aspect ratios, the coupling of laminar natural convection and surface radiation has been widely studied [17][18][19][20][21][22][23][24][25]. In general, these studies have shown that surface radiation considerably modifies the dynamic and thermal fields with a reduction in the convective heat transfer but a significant increase of the overall heat transfer between the active walls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal phenomenon induced by this type of heat transfer is an interesting question for many studies focusing on building thermal area. [1][2][3][4][5][6][7] Further studies have been conducted investigating combined convection/conduction in other engineering fields such as heat exchangers. [8][9][10] Also, gas turbine design and their operation mode involves a very precise analysis of conjugate heat transfer for temperature field prediction and better cooling of turbine components.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is implicated in several industrial applications and has a very wide research interest. The thermal phenomenon induced by this type of heat transfer is an interesting question for many studies focusing on building thermal area 1‐7 . Further studies have been conducted investigating combined convection/conduction in other engineering fields such as heat exchangers 8‐10 .…”
Section: Introductionmentioning
confidence: 99%